Investigating the Origin of the First Ionization Potential Effect With a Shell Turbulence Model - Réville, Victor; Rouillard, Alexis P.; Velli, Marco; Verdini, Andrea; Buchlin, Éric; Lavarra, Michael; Poirier, Nicolas (Frontiers in Astronomy and Space Sciences, 2021)
The enrichment of coronal loops and the slow solar wind with elements that have low First Ionization Potential, known as the FIP effect, has often been interpreted as the tracer of a common origin. A current explanation for this FIP fractionation rests on the influence of ponderomotive forces and turbulent mixing acting at the top of the chromosphere. The implied wave transport and turbulence mechanisms are also key to wave-driven coronal heating and solar wind acceleration models. This work makes use of a shell turbulence model run on open and closed magnetic field lines of the solar corona to investigate with a unified approach the influence of magnetic topology, turbulence amplitude and dissipation on the FIP fractionation. We try in particular to assess whether there is a clear distinction between the FIP effect on closed and open field regions.